Inhibitory mechanism of the nucleus of the solitary tract involved in the control of cardiovascular, dipsogenic, hormonal, and renal responses to hyperosmolality - Blanch, Graziela T. [UNESP]; Freiria-Oliveira, André H. [UNESP]; Murphy, David; Paulin, Renata F.; Antunes-Rodrigues, José; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP]; Colombari, Débora S.A. [UNESP] (American Physiological Society, 2013)
The nucleus of the solitary tract (NTS) is the primary site of visceral afferents to the central nervous system. In the present study, we investigated the effects of lesions in the commissural portion of the NTS (commNTS) on the activity of vasopressinergic neurons in the hypothalamic paraventricular (PVN) and supraoptic (SON) nuclei, plasma vasopressin, arterial pressure, water intake, and sodium excretion in rats with plasma hyperosmolality produced by intragastric 2 M NaCl (2 ml/rat). Male Holtzman rats with 15-20 days of sham or electrolytic lesion (1 mA; 10 s) of the commNTS were used. CommNTS lesions enhanced a 2 M NaCl intragastrically induced increase in the number of vasopressinergic neurons expressing c-Fos in the PVN (28 ± 1, vs. sham: 22 ± 2 c-Fos/AVP cells) and SON (26 ± 4, vs. sham: 11 ± 1 c-Fos/AVP cells), plasma vasopressin levels (21 ± 8, vs. sham: 6.6 ± 1.3 pg/ml), pressor responses (25 ± 7 mmHg, vs. sham: 7 ± 2 mmHg), water intake (17.5 ± 0.8, vs. sham: 11.2 ± 1.8 ml/2 h), and natriuresis (4.9 ± 0.8, vs. sham: 1.4 ± 0.3 meq/1 h). The pretreatment with vasopressin antagonist abolished the pressor response to intragastric 2 M NaCl in commNTS-lesioned rats (8 ± 2.4 mmHg at 10 min), suggesting that this response is dependent on vasopressin secretion. The results suggest that inhibitory mechanisms dependent on commNTS act to limit or counterbalance behavioral, hormonal, cardiovascular, and renal responses to an acute increase in plasma osmolality. © 2013 the American Physiological Society.
Keywords: Blood pressure; C-Fos expression; Osmoreceptor; Thirst; Vasopressin; sodium chloride; vasopressin; vasopressin antagonist; oxytocin; protein c fos; vasopressin derivative; animal experiment; animal model; animal tissue; arterial pressure; brain stem injury; cardiovascular function; heart rate; hormone action; hormone blood level; hyperosmolality; hypothalamic paraventricular nucleus; kidney function; male; nonhuman; priority journal; rat; solitary tract nucleus; solitary tract nucleus lesion; thirst; animal; blood pressure; cytology; drinking; genetics; kidney; metabolic disorder; metabolism; osmolarity; physiology; Sprague Dawley rat; supraoptic nucleus; Animals; Blood Pressure; Drinking; Kidney; Male; Osmolar Concentration; Oxytocin; Paraventricular Hypothalamic Nucleus; Proto-Oncogene Proteins c-fos; Rats; Rats, Sprague-Dawley; Solitary Nucleus; Supraoptic Nucleus; Vasopressins; Water-Electrolyte Imbalance